Premature ovarian failure after childhood cancer and risk of metabolic syndrome: a cross-sectional analysis. Issue 1 (21st May 2021) - Netterlid, Axel; Mörse, Helena; Giwercman, Aleksander; Henic, Emir; Åkesson, Kristina E; Erfurth, Eva-Marie; Elfving, Maria
Abstract : Objective: Female childhood cancer survivors (CCS) are at risk of several late effects, such as metabolic syndrome (MetS) and premature ovarian insufficiency (POI). The objective is to study if POI is associated with risk of MetS and increased cardiovascular risk in CSS. Design: A cross-sectional study with a median time since the cancer diagnosis of 25 (12–41) years. Patients and controls were recruited from the South Medical Region of Sweden. Methods: The study included 167 female CCS, median age 34 (19–57) years, diagnosed with childhood cancer at median age 8.4 (0.1–17.9) years together with 164 controls, matched for age, sex, ethnicity, residence, and smoking habits. All subjects were examined with fasting glucose, insulin, HbA1c, and lipid profile. Fat mass was calculated with dual-energy X-ray absorptiometry (DXA), and questionnaires for medication were obtained. Detailed information of cancer treatment was available. Results: POI was present in 13% (22/167) among CCS (hypothalamic/pituitary cause excluded) and in none among controls. MetS was present in 14% (24/167) among all CCS ( P   = 0.001), in 23% (5/22) of those with POI ( P   < 0.001), compared with 4% (6/164) among controls. OR for MetS in all CCS compared with controls was 4.4 (95% CI: 1.8, 11.1) ( P   = 0.002) and among CCS with POI the OR was 7.7 (CI: 2.1, 28.1) ( P   = 0.002). Conclusion: The prevalence of MetS was higher in females treated for childhood cancer compared with controls, and the presence of POI significantly increased the risk of developing MetS.